2009
DOI: 10.1002/bjs.6608
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of surgical treatment for fistula in ano in Crohn's disease

Abstract: Surgical outcome for high or complex Crohn's fistula in ano remains disappointing, and recurrence is unpredictable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 20 publications
3
43
2
2
Order By: Relevance
“…One study29 found that 22 of 27 patients had a ‘satisfactory’ outcome, although the five patients in whom the outcome was unsuccessful developed significant incontinence. Higher rates of continence disturbance were seen in other studies30.…”
Section: Resultsmentioning
confidence: 41%
See 4 more Smart Citations
“…One study29 found that 22 of 27 patients had a ‘satisfactory’ outcome, although the five patients in whom the outcome was unsuccessful developed significant incontinence. Higher rates of continence disturbance were seen in other studies30.…”
Section: Resultsmentioning
confidence: 41%
“…Longer‐term (6 months or more after treatment) fistula recurrence occurred in five of 28 patients30 and three of nine patients46 at 12 months. One study29 found that 22 of 27 patients had a ‘satisfactory’ outcome, although the five patients in whom the outcome was unsuccessful developed significant incontinence.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations